Alkaloidal constituents of Tinospora crispa - Choudhary, M. Iqbal; Ismail, Muhammad; Ali, Zulfiqar; Shaari, Khozirah; Lajis, Md. Nordin; Atta-ur-Rahman, (Natural Product Communications, 2010)
Phytochemical investigations of the stems of Tinospora crispa led to the isolation of one new aporphine alkaloid, N-formylasimilobine 2-O-beta-D-glucopyranoside (1), along with six known alkaloids, N-formylasimilobine 2-O-beta-D-glucopyranosyl-(1 --> 2)-beta-D-glucopyranoside (2) (tinoscorside A), N-formylanonaine (3), N-formyldehydroanonaine (4), N-formylnomuciferine (5), N-demethyl-N-formyldehydronornuciferine (6), magnoflorine (7), paprazine (8), N-trans-feruloyltyramine (9), and cytidine (10). The structure of new compound 1 was deduced on the basis of spectroscopic data.